2011
DOI: 10.3109/00048674.2010.541418
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Studies of Cognition in First Episode Psychosis: A Systematic Review of the Literature

Abstract: Although cognitive deficits are recognized as a core feature in schizophrenia, their evolution over the course of the illness is still debated. Longitudinal studies of cognition in patients after a first episode of psychosis (FEP) provide extremely useful information, in that they include an adequate and realistic baseline measure of cognitive performance, while at the same time minimizing the effect of confounding variables associated with chronicity. The aim of this systematic review was to summarize finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
123
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(136 citation statements)
references
References 84 publications
11
123
1
1
Order By: Relevance
“…The comprehensive deficits in cognitive capacity in individuals with psychosis are consistent with the literature, specifically a reduced improvement in processing speed and verbal learning over time relative to other cognitive domains has previously been reported (Juuhl-Langseth et al, 2014;Rodríguez-Sánchez et al, 2013;Bozikas and Andreou, 2011), although not uniformly (Leeson et al, 2009). Stability in the remaining cognitive deficits has also been identified in measures of attention Ayesa-Arriola et al, 2013) social cognition (Horan et al, 2012) working memory de Mello Ayres et al, 2010) reasoning and problem solving (Juuhl-Langseth et al, 2014) and visual learning .…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The comprehensive deficits in cognitive capacity in individuals with psychosis are consistent with the literature, specifically a reduced improvement in processing speed and verbal learning over time relative to other cognitive domains has previously been reported (Juuhl-Langseth et al, 2014;Rodríguez-Sánchez et al, 2013;Bozikas and Andreou, 2011), although not uniformly (Leeson et al, 2009). Stability in the remaining cognitive deficits has also been identified in measures of attention Ayesa-Arriola et al, 2013) social cognition (Horan et al, 2012) working memory de Mello Ayres et al, 2010) reasoning and problem solving (Juuhl-Langseth et al, 2014) and visual learning .…”
Section: Discussionsupporting
confidence: 77%
“…In general, it has been shown that the majority of cognitive deficits remain stable following an initial psychotic episode (Bozikas and Andreou, 2011;Bora and Murray, 2013), although there is variability throughout the literature. For example, verbal learning has variously been reported to either remain stable over 3 years , to deteriorate over 10 years and 13 years (Bozikas andAndreou, 2011, Øie et al, 2010); or to improve over 6 months and 2 years (Jahshan et al, 2010;Barder et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurocognitive deficits are considered the most stable aspect of schizophrenia, with test-retest coefficients ranging from 0.70 to 0.85 (Albus et al, 2002;Bozikas & Andreou, 2011;Censits, Ragland, Gur, & Gur, 1997;Hoff et al, 1999). The stability of these deficits has been established in numerous studies.…”
Section: Advantages Of Cognitive Subtypingmentioning
confidence: 99%
“…2 They start as early as the prodromal state 3 and may remain relatively stable over time after the first episode of psychosis. 4 Despite substantial research efforts, the origin of working memory disturbances in patients with schizophrenia remains obscure. In fact, these disturbances cannot be fully explained by clinical factors, such as duration of illness, antipsychotic medication or symptom profile.…”
Section: Introductionmentioning
confidence: 99%